Directed self-assembly of herbal small molecules into sustained release hydrogels for treating neural inflammation - Jun Zheng (Nature Communications, 2019)
There is interest in the development of drug-based hydrogels for responsive sustained drug release. Here, the authors report on the self-assembly of natural small molecule, rhein, into hydrogels and the application of the hydrogels as stable controlled release agents for neuro-inflammatory therapy